2007
DOI: 10.1016/j.nbd.2006.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dysfunction in the R6/2 mouse model of Huntington’s disease

Abstract: Recent evidence suggests that mutant huntingtin protein-induced energetic perturbations contribute to neuronal dysfunction in Huntington's disease (HD). Given the ubiquitous expression of huntingtin, other cell types with high energetic burden may be at risk for HD-related dysfunction. Early-onset cardiovascular disease is the second leading cause of death in HD patients; a direct role for mutant huntingtin in this phenomenon remains unevaluated. Here we tested the hypothesis that expression of mutant huntingt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
116
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 93 publications
(98 reference statements)
10
116
0
6
Order By: Relevance
“…In pre-clinical settings, the R6/2 mouse model -that displays impairment in cardiac functions -had significant alterations in mitochondrial structure, including the loss of mitochondrial elongated shapes and diffused mitochondrial densities [36,37]. These morphological changes may lead directly to cardiac energy metabolism imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…In pre-clinical settings, the R6/2 mouse model -that displays impairment in cardiac functions -had significant alterations in mitochondrial structure, including the loss of mitochondrial elongated shapes and diffused mitochondrial densities [36,37]. These morphological changes may lead directly to cardiac energy metabolism imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…The aggressive phenotype makes R6/2 very useful for preclinical pharmacology, but it is not an exact genetic or neuropathological analog of HD. R6/2 mice have widespread NII expression, a high incidence of epilepsy, diabetes, cardiac dysfunction, and neuromuscular junction abnormalities (Hurlbert et al, 1999;Meade et al, 2002;Ribchester et al, 2004;Mihm et al, 2007). The R6/2 line is a plausible model of juvenile-onset HD, in which the effects of the expanded polyglutamine repeat occurs in the context of a developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…The best example of this hypothesis is Huntington disease, an autosomal dominant condition resulting from the expansion of the tri nucleotide CAG repeat ('polyQ repeat') in the hunting tin (HTT) gene. HF is among the leading causes of death in Huntington disease 114 , and the prevalence of HF in patients with Huntington disease is markedly increased com pared with age matched controls 115 [118][119][120] have demonstrated that whole body expression of polyQ proteins precipitates cardiomyopathy. Although this observation supports a direct involvement of the mutant huntingtin in development of cardiac disease, Huntington disease also features marked imbalance in the autonomic nervous system, leading to enhanced sympathetic tonus 121 , which might (partly) contribute to HF in Huntington disease.…”
Section: Derailment Owing To Genetic Mutationsmentioning
confidence: 99%